Characterization of novel lectins from Burkholderia pseudomallei and Chromobacterium violaceum with seven-bladed β-propeller fold - Sýkorová, Petra; Novotná, Jitka; Demo, Gabriel; Pompidor, Guillaume; Dubská, Eva; Komárek, Jan; Fujdiarová, Eva; Houser, Josef; Hároníková, Lucia; Varrot, Annabelle; Shilova, Nadezhda; Imberty, Anne; et al. (International journal of biological macromolecules, 2020)
Burkholderia pseudomallei and Chromobacterium violaceum are bacteria of tropical and subtropical soil and water that occasionally cause fatal infections in humans and animals. Microbial lectins mediate the adhesion of organisms to host cells, which is the first phase in the development of infection. Here we report the discovery of two novel lectins from the above-mentioned bacteria - BP39L and CV39L. The crystal structures revealed that the lectins possess a seven-bladed β-propeller fold. Functional studies conducted on a series of oligo- and polysaccharides confirmed the preference of BP39L for mannosylated saccharides and CV39L for rather more complex polysaccharides with a monosaccharide preference for β-l-fucose. The presented data indicate that the proteins belong to a currently unknown family of lectins.
Keywords: Chromobacterium; Bacterial Proteins; bakteriální proteiny; Monosaccharides; Animals; monosacharidy; lidé; Fucose; Humans; fukosa; Polysaccharides; zvířata; Lectins; lektiny; Burkholderia pseudomallei; polysacharidy